Pengaruh Pemeraman Buah dan Periode Simpan terhadap Viabilitas Benih Pepaya (Carica papaya L.) - Endang Murniati; Maryati Sari; Ema Fatimah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The objective of this experiment was to study the influence of post-harvest storage and storage period to seed viability. The research was conducted in the Laboratory of Seed Science and Technology and the green house at Leuwikopo IPB Darmaga, from February until August 2007. The experiment used split-plot design with three replications. The main plot was seven periods of storage: 0, 3, 6, 9, 12, 15, and 18 weeks. The sub plot was the period of post-harvest maturation storage (use the fruits with 30-40% yellow coloured): 0, 2, 4, 6 days post-harvest storage, and control fruits that ripe on the tree (with 80-90% yellow coloured). The control fruits have the best seed viability and vigor. Viability of seed from fruits with 0, 2 and 6 days post-harvest storage was significantly less than that of control. Seed from four days post-harvest storage have same viability as control. Post-harvest storage can improve physiological seed quality on the seed that must be harvested before the time of physiological maturity, especially four days post-harvest storage